2010
DOI: 10.1016/j.ejcts.2010.01.065
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial appendage contributes to left atrial booster function after the maze procedure: quantitative assessment with multidetector computed tomography☆

Abstract: LAA largely contributes to LA booster function, particularly in the maze group, because LA booster function is deteriorated in this group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
(18 reference statements)
1
6
0
1
Order By: Relevance
“…In the present study, the LAA demonstrated the highest contractility among the three anatomic compartments. A previous report has stated that LAA preservation contributes to an improved contractile function of the LAA after MAZE procedure [5]. In the present study, the LAA parameters displayed a relatively poor relationship with those of the left atrial proper, which is consistent with a previous report stating that the LAA has a distinct pattern of contraction and a greater dependence on LV function than on LA function [11].…”
Section: The Anatomy and Function Of The Laa In Control And Af Patientssupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, the LAA demonstrated the highest contractility among the three anatomic compartments. A previous report has stated that LAA preservation contributes to an improved contractile function of the LAA after MAZE procedure [5]. In the present study, the LAA parameters displayed a relatively poor relationship with those of the left atrial proper, which is consistent with a previous report stating that the LAA has a distinct pattern of contraction and a greater dependence on LV function than on LA function [11].…”
Section: The Anatomy and Function Of The Laa In Control And Af Patientssupporting
confidence: 93%
“…Because the structure of the LA differs according to each compartment, it is necessary to understand the physiological changes that can occur in each LA compartment. The LAA is known to be important to preserve a contractile function and to serve as a main source of thrombus formation in AF patients [5]. However, functional assessments of the ALA and VLA have not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Между тем максимальный объем ушка левого предсердия в первой группе был значительно больше (16,9±7,3 мл против 8,4±4,7 мл), но фракция вы-броса ушка (34,1±12,8% против 36,1±7,4%) была сопоста-вима в обеих группах, таким образом, вклад ушка левого предсердия является значимым, особенно у пациентов, перенесших РЧ-процедуру «Лабиринт», т.к. показатели сократимости левого предсердия в целом у них хуже [34].…”
Section: особенности хирургического лечения длительно персистирующей unclassified
“…Kamohara and coworkers described that LAA exclusion may affect left atrial reservoir function in short- and mid-term periods in animal models [72]. Yamanaka and coworkers reported the influence of LAA exclusion on left atrial function by computed tomography [73]. In their study, LAA preservation contributed to improved transport function, and none of their patients in sinus rhythm after the maze procedure experienced a thromboembolic event.…”
Section: Left Atrial Appendage Managementmentioning
confidence: 99%